Mediating effect of social participation in the association between cognitive frailty and health-related quality of life among hospitalized older adults: a cross-sectional study in Xi’an, China - Zhaozhao Hui; Yayi Zhao; Qianhui Gong; Yajing Li; Feng Liu; Xiaoyun Zhao; Xiaohong Liu (BMC Geriatrics)
Abstract Background Cognitive frailty, the co-occurrence of physical frailty and cognitive impairment, has emerged as an essential factor affecting the health-related quality of life (HRQoL) among older adults; however, the role of social participation remains unknown. Our study aimed to explore the mediating role of social participation in the association between cognitive frailty and HRQoL among hospitalized older adults. Methods A total of 467 older adults were recruited from three tertiary hospitals in Xi’an, China. Cognitive frailty was ascertained by the FRAIL scale and the Montreal Cognitive Assessment. Social participation was assessed by the questionnaire that was developed based on the China Health and Retirement Longitudinal Study. HRQoL was measured by the 36-item Short Form Health Survey. Bootstrap mediation effects were employed to estimate the mediating effect of social participation in the association between cognitive frailty and HRQoL. Results The average age of the participants was 70.8 years and 51.8% were female. Individuals with cognitive frailty had significantly lower levels of social participation (5.9 ± 3.7 vs. 7.8 ± 4.1) and HRQoL (57.8 ± 15.5 vs. 68.1 ± 13.9) (physical component summary [PCS]: 52.4 ± 19.0 vs. 66.0 ± 16.7; mental component summary [MCS]: 63.2 ± 16.5 vs. 70.2 ± 15.4) compared to those without cognitive frailty. Social participation partially mediated the association between cognitive frailty and HRQoL (average causal mediation effect [ACME] = –1.22, 95% confidence interval [CI]: − 2.20, −0.51) as well as on its dimensions of PCS (ACME = –1.12, 95% CI: − 2.13, − 0.55) and MCS (ACME = –1.29, 95% CI: − 2.35, − 0.49). Gender moderated the mediating effect of social participation in the association between cognitive frailty and HRQoL, which was more pronounced in women than that in men. Conclusions The findings suggest that social participation mediates the association between cognitive frailty and HRQoL, particularly for women. This study expands the current literature on designing policy solutions to promote participation in social activities among older adults with cognitive frailty, with the goal of maintaining their HRQoL at a favorable level.